2013
DOI: 10.1021/bm401521f
|View full text |Cite
|
Sign up to set email alerts
|

Terpene and Dextran Renewable Resources for the Synthesis of Amphiphilic Biopolymers

Abstract: The present work shows the synthesis of amphiphilic polymers based on the hydrophilic dextran and the hydrophobic terpenes as renewable resources. The first step concerns the synthesis of functional terpene molecules by thiol-ene addition chemistry involving amino or carboxylic acid thiols and dihydromyrcenol terpene. The terpene-modified polysaccharides were subsequently synthesized by coupling the functional terpenes with dextran. A reductive amination step produced terpene end-modified dextran with 94% of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 48 publications
0
32
0
Order By: Relevance
“…The thiol-ene 'click' reaction between limonene and various thiols has been discussed in a number of different publications previously. 31 In our hands, however, while the 1 H NMR spectroscopic analysis of the product of the reaction between PETMP and limonene confirmed the preferential addition of the thiol to the exocyclic alkene (in preference to the endocyc- lic alkene), in contrast to the observation of chemoselective addition to the exocyclic alkene observed by Firdaus et al, 30 our results indicate that about 27% of the endo-alkene moieties react with the thiol compared to 93% of the exo-alkene species (ESI Table 1 †). Extension of this study to other terpenes revealed that in linalool, the addition of thiols was more evenly distributed between the alkenes with 93% tri-substituted alkene and 80% di-substituted alkene consumed (ESI Table S2, Fig.…”
Section: Resin Synthesis and Crosslinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The thiol-ene 'click' reaction between limonene and various thiols has been discussed in a number of different publications previously. 31 In our hands, however, while the 1 H NMR spectroscopic analysis of the product of the reaction between PETMP and limonene confirmed the preferential addition of the thiol to the exocyclic alkene (in preference to the endocyc- lic alkene), in contrast to the observation of chemoselective addition to the exocyclic alkene observed by Firdaus et al, 30 our results indicate that about 27% of the endo-alkene moieties react with the thiol compared to 93% of the exo-alkene species (ESI Table 1 †). Extension of this study to other terpenes revealed that in linalool, the addition of thiols was more evenly distributed between the alkenes with 93% tri-substituted alkene and 80% di-substituted alkene consumed (ESI Table S2, Fig.…”
Section: Resin Synthesis and Crosslinkingmentioning
confidence: 99%
“…[19][20][21][22] This class of monomer is widely available, and may be found in essential oils, tree sap and materials, citrus fruit, and even as by-products from other manufacturing processes, such as the paper industry's Kraft process, or simply through the processing of citrus fruits and other renewable resources. [23][24][25][26] The inherent double bonds present in mono-, di-, tri-, and other polyterpenes make them excellent candidates for the creation of sustainably-sourced photo-crosslinkable resins, yet to date only a few studies have investigated their application beyond utilizing appended (meth)acrylate or epoxide functionalities for (controlled) radical polymerisation 27,[28][29][30] modified polysaccharides, 31 polycarbonates, 32 and even polysilanes, 33 with processing still being limited in such studies. Herein, we report our study of the application of five terpenes: limonene, terpinene, geraniol, nerol and linalool ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…4 On the other hand, terpenes or terpenoids refer to one of the largest families of naturally occurring compounds and are secondary metabolites synthesized mainly by plants, particularly conifers. 8 To make use of the chemical functionalities (unsaturation, functional groups) present in terpene molecules, various chemical strategies and a wide range of polymerisation techniques [9][10][11][12][13][14][15][16][17][18][19] had been studied. Thus, due to their abundance in nature, there has been great interest in producing polymers with terpenes as either functional entities or as the main constituent.…”
Section: Introductionmentioning
confidence: 99%
“…45–97 %), and β‐pinene (ca. 0.5–28 %), are useful raw materials that are industrially converted into value‐added compounds through a variety of chemical modifications . Besides pinenes, limonene, a cyclic diene monoterpene, is also a valuable compound that is typically obtained from citrus peel .…”
Section: Terpenes As Promising Renewable Platform Chemicalsmentioning
confidence: 99%
“…Amphiphilic polymers have been prepared from the combination of two renewable starting materials, hydrophilic dextran and hydrophobic terpenes . The initial step involved a quantitative thiol–ene addition of cysteamine hydrochloride or 3‐mercaptopropionic acid to dihydromyrcenol ( 31 ) by using AIBN as a thermal initiator, thereby affording two kinds of terpenes that contain an amino group ( 32 ) or a carboxylic acid group ( 33 ; Scheme ).…”
Section: Thiol–ene Reaction For the Synthesis Of Terpene‐based Monomementioning
confidence: 99%